Evaluation of outcome of mode of delivery in severe preeclampsia - K. S., Raveena; S. R., Sheela (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Preeclampsia is new onset hypertension of more than 140/90 mmHg on 2 occasions, 4 hours apart in pregnancy, which occurs after 20 weeks of gestation and frequently near term. If there are other symptoms like as headache, blurred vision from end organ damage, and thrombocytopenia, it is characterized as severe preeclampsia. Regardless of the foetal outcome, treatment for severe preeclampsia is immediate delivery. The goal of the current study is to assess how different delivery methods affect individuals with severe preeclampsia. Methods: It is a retrospective study conducted in RL Jalappa hospital, Kolar from January 2021 to February 2022. Out of 2568 deliveries at our facility throughout the study period, 150 singleton pregnancies complicated by severe preeclampsia delivered at 24-34 weeks of gestation were chosen for the study. Women who had additional obstetric, foetal, or medical difficulties were not included in the study. Results: 110 study participants had an LSCS form of delivery out of the total. Among them, non-reassuring fetal heart rate, obstructed labor, and malpresentation were the most typical indicators for LSCS. The difference between Bishop’s score and the mode of delivery was statistically significant. There was no discernible difference between the newborn’s APGAR score immediately following delivery and the method of delivery. Conclusions: There are strong chances of a normal vaginal birth if the Bishop score at the time of admission and induction is more than 4.